Integrated virologic analysis of resistance to nirmatrelvir/ritonavir in individuals across four phase 2/3 clinical studies for the treatment of COVID-19Research in context - Mary Lynn Baniecki; Shunjie Guan; Devendra K. Rai; Qingyi Yang; Jonathan T. Lee; Li Hao; Edward Weinstein; Craig Hyde; Rhonda D. Cardin; Holly Soares; Jennifer Hammond (EBioMedicine, 2025)
Summary: Background: SARS-CoV-2 resistance to nirmatrelvir/ritonavir (NMV/r) surveillance is essential to identify emergence and track treatment-resistance. Methods: This integrative virologic analysis across EPIC (Evaluation of Protease Inhibition of COVID-19) phase 2/3 clinical studies (-High Risk [HR], -Standard Risk [SR], -Immunocompromised [IC], -Retreatment) used next-generation sequencing to identify SARS-CoV-2 variants and Mpro or cleavage site emergent substitutions (ES). Treatment ES (TES) and ES in patients experiencing COVID-19‒related hospitalisation or viral RNA rebound were evaluated for in vitro NMV resistance, structure analysis, and global incidence via GISAID EpiCoV SARS-CoV-2 database. Findings: Sequences were evaluated in 1605 NMV/r, 1216 placebo (PBO), and 114 PBO/r-treated participants. NMV/r Mpro TES were observed in EPIC-HR/SR (pooled) (T98I/R/del [n = 4], E166V [n = 3], W207L/R/del [n = 4]), cleavage (A5328 S/V [n = 7], S6799 A/P/Y [n = 4]). PBO cleavage ES were observed (A5328T [n = 1], S6799F [n = 1]). Among hospitalised NMV/r-treated participants (EPIC-HR [n = 10], –SR [n = 5], –IC [n = 2], –Retreatment [n = 0]), 2 Mpro ES were observed: A260T (EPIC-HR [n = 1]), K269R (EPIC-SR [n = 1]). In EPIC-IC, 3 Mpro ES (T98S, A191V, T201I) and 2 cleavage site ES (A4136V, S4145N) were observed with rebound. E166V was the only TES associated with resistance (NMV/r: HR [n = 3]; PBO/r: –Retreatment [n = 1]), but not in participants experiencing hospitalisation or with immunocompromising conditions. Global E166V incidence was rare (<0.001% in pre- and post-NMV/r emergency use authorization) by GISAID (December 1, 2019–June 30, 2024). Interpretation: In EPIC, NMV-resistance mutations were infrequent. E166V was the only resistance-associated substitution but was not identified in participants experiencing hospitalisation or with immunocompromising conditions. NCT04960202, NCT05011513, NCT05438602, NCT05567952. Funding: Pfizer Inc.